Extraterritorial Application of the Securities Acts (Washington University Law Quarterly, 1974)
The federal securities laws, and the 1934 Act in particular, have only recently been applied to transactions that are substantially extraterritorial. During the last ten years, however, the courts have increasingly accepted jurisdiction over securities violations that involve small amounts of local “conduct” or “effect.” Between the relatively clear situations in which both significant conduct and effect occur either domestically or outside the United States, the courts have struggled to develop a workable and predictable standard for imposing American jurisdiction to protect both American investors and the integrity of laws regulating domestic securities transactions, without violating principles of international law. The result has been, in general, to focus on the degree of conduct within this country and the role of that conduct within the overall transaction giving rise to a securities claim. Yet, the courts have been reluctant to abandon a requirement of at least some domestic effect.
Keywords: Extraterritoriality; Securities; Jurisdiction